2022
DOI: 10.1136/gutjnl-2021-326599
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota changes are detected in asymptomatic very young children with SARS-CoV-2 infection

Abstract: We read with great interest the recent article by Yeoh et al, demonstrating an altered stool microbiome composition in patients with COVID-19 compared with controls, with greater dysbiosis correlating with elevated inflammatory markers. 1 Additionally, dysbiosis was seen after disease resolution. 1 To our knowledge, gut microbiome studies in young children with COVID-19 have not been reported. Critically, the developing gut microbiome of very young children differs from adults and establishes immune and inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 10 publications
(21 reference statements)
1
16
0
Order By: Relevance
“…The composition of the oral microbiome is established early in life, is stable throughout life ( 65, 66 ), and it has implications for long-term health ( 67, 68 ). Despite oral microbiota changes in infants, we did not observe an effect of SARS-CoV-2 infection during pregnancy on the offspring’s gut microbiota, similar to previously reported ( 69 ). However, we observed that infants born to pregnant women with active infection presented elevated fecal calprotectin levels indicative of a pro-inflammatory tone early in life.…”
Section: Discussionsupporting
confidence: 90%
“…The composition of the oral microbiome is established early in life, is stable throughout life ( 65, 66 ), and it has implications for long-term health ( 67, 68 ). Despite oral microbiota changes in infants, we did not observe an effect of SARS-CoV-2 infection during pregnancy on the offspring’s gut microbiota, similar to previously reported ( 69 ). However, we observed that infants born to pregnant women with active infection presented elevated fecal calprotectin levels indicative of a pro-inflammatory tone early in life.…”
Section: Discussionsupporting
confidence: 90%
“…Preliminary data showed that an altered gut microbiome in nine children with COVID-19 aged between 7 and 139 months was dominated by the genus Pseudomonas , and this change persisted for weeks after hospital discharge 45 . In 12 asymptomatic young children aged 0–24 months with SARS-CoV-2 infection, depletion of Bifidobacterium bifidum and Akkermansia muciniphila , which are linked to protection against inflammation, were observed in SARS-CoV-2-positive faecal samples 46 . Multisystem inflammatory syndrome in children (MIS-C) associated with COVID-19 has been increasingly recognized 47 .…”
Section: Covid-19 and Gut Microbiotamentioning
confidence: 99%
“…“Long COVID” is the new evidence. The gut microbiome changes are linked to disease severity both in adult patients and young children with COVID-19 ( Yeoh et al, 2021 ; Nashed et al, 2022 ; Sun et al, 2022 ). Several gut commensals microbiota with known immunomodulatory potential were underrepresented in patients and remained low in samples collected up to 30 days after disease resolution.…”
Section: Discussionmentioning
confidence: 99%